The management of Bhawal National Park, Bangladesh by the local community for resource protection and ecotourism - Mohd, Abdullah (Canadian Center of Science and Education, 2008)
Local community participation in ecotourism activities and resource protection and in protected areas can be pursued through collaborative management At present, the natural resources of the park are degrading due to indiscriminate use by the locals and visitors mainly in the form of encroachment and tourism incompatible activities. The local community was left out in decision making process where the core problem still not addressed. This study investigates the problems that affected natural resources and local community involvement in management to mitigate such problem. A survey was conducted in Bhawal National Park (BNP), Bangladesh in December 2006 to February 2007 involved 215 respondents comprising of personnel of the National Park and local community. The respondents include nature guides, food and transportation providers. It is administered by using structured interview questionnaires to elicit opinions from the respondents based on convenient sampling technique. Various statistical analysis namely Exploratory Data Analysis (EDA), Descriptive statistics, Chi-square (?²), Mann-Whitney test and Kruskal-Wallis test (non-parametric) were used for data analysis. Results showed that the relationship between the local community and park administration is not significant where their participation in the management is minimal. In overall the study provides the premises where the local community supported their participation in the decision making process and participate in management for a better stewardship of the park.